Temporally Separated Data Sets Reveal Similar Traits of Birds Persisting in a United States Megacity - Cooper, Daniel S.; Shultz, Allison J.; Blumstein, Daniel T. (Frontiers in Ecology and Evolution, 2020)
We present an analysis of life history and behavioral traits associated with urbanization for 53 breeding bird species on 173 survey blocks in the Los Angeles area of southern California, USA, across two time periods, 1995–99 and 2012–16. We used observational data from two community science efforts and an estimate of urban land cover in each block to develop an index of urban association, and then modeled the relationship between species occurrence and eight traits likely associated with urban tolerance. We found two traits to be significantly associated with urbanization in both eras: Structure-nesting (i.e., the tendency to build nests on human-built structures) was positively associated, and cavity-nesting (i.e., the tendency to build nests in natural tree cavities) was negatively associated. Our analysis provides a template for mining historical community science data, and for “retrofitting” contemporary data to gain insights into ecological trends over time, and illustrates the persistence of ecological traits of species associated with urban areas even as the makeup of these species communities may change.